P.057 Multidisciplinary Care for Optimal Management of Complex Nerve Injuries In Canada. (November 2021) - Chapman, K; Doherty, C; Bristol, SG; O'Connor, R; Berger, MJ
Abstract : Background: Recent advances in management of peripheral nerve injuries is leading to a paradigm shift in the treatment of Canadian patients. Multi-disciplinary care models provide diagnostic, surgical and rehabilitative consultations within a single clinical encounter. Involvement of allied health care professionals has been shown to improve outcome. The purpose of this study was to ascertain the distribution and composition of multidisciplinary teams, and identify regional disparities. Methods: Representatives from clinics across Canada were invited to participate in a survey at the Annual Canadian Peripheral Nerve Symposium in London, Ontario in November 2019, with telephone follow up. Results: Delegates from 17 programs responded to the survey (12 academic centre and 5 community setting). Program provides electrodiagnostic testing, neuromuscular, rehabilitation and surgical assessment. Access to the following services was reported: occupational therapy=53% (9/17), physiotherapy 29% (5/17), research assistant=17% (3/17), social work=12% (2/17), mental health=6% (1/17). Conclusions: Complex nerve injury clinics are being established throughout Canada. Allied health care and research support are limited in many multi-disciplinary complex nerve injury programs. There is variable access, likely resulting in disparities in patient care across Canada. This data will be valuable for lobbying for resources for resources to improve the care of these complex patients.